Synthesis, Structure, and Reactivity of 5‐(Aryl)dibenzothiophenium Triflates. (26th November 2019) - Kafuta, Kevin; Korzun, André; Böhm, Marvin; Golz, Christopher; Alcarazo, Manuel
Abstract: A synthetic protocol for the preparation of 5‐(aryl)dibenzothiophenium salts starting from inexpensive dibenzothiophene S ‐oxide and simple arenes is reported. The scope of the method regarding the nature of the arene is evaluated, intermediates along the reaction sequence have been trapped, and side‐reactions identified. In addition, the X‐ray structures of a complete set of these salts are reported and their reactivities studied. Specifically, chemoselective Suzuki coupling is observed at the dibenzothiophenium in the presence of iodides. Abstract : Durch hochselektive metallfreie C‐H‐Sulfenylierung von Arenen wurden 5‐(Aryl)dibenzothiopheniumtriflate hergestellt. Diese Salze gehen eine ortsselektive Suzuki‐Miyaura‐Kupplung in Gegenwart von C‐I‐Bindungen ein, was die iterative Synthese von Polyarenen ermöglicht.